Spain : Selected Issues. (IMF Staff Country Reports; Country Report, 2009)
Spain's housing boom was supported by rapid economic expansion, strong employment growth, an immigration boom, and low real interest rates. With the abrupt drying up of funding since mid-2007, these factors have eroded quickly. Through 2010, employment and value added in construction are projected to halve as peak housing starts are completed. The authorities have launched efforts to help limit foreclosures and to activate the underdeveloped rental market. In the medium term, housing market cyclicality could be reduced by fading out generous home ownership incentives.